2016
DOI: 10.1007/s11356-016-6603-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of WWII dumpsites on Saipan (CNMI): heavy metal status of soils and sediments

Abstract: A number of dumpsites occur on the island of Saipan and in the surrounding coastal waters. Many of these sites date back to the immediate post WWII clean-up period and contain a variety of wartime wastes. Metallic debris is generally the most visible waste material and commonly includes bomb fragments, artillery shells, bullets, and other military hardware. In this investigation, we examined the heavy metal status of soils from around several of these dumpsites and in any obvious drainage pathways leading from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The soil concentrations of contaminants in military zones and war-impacted areas in literature have been typically compared to various types of defined values: (1) background soil concentrations [13,[15][16][17][18][19][20], (2) agricultural soil concentrations [9,17,21,22], (3) generic industrial, urban, and/or recreational soil concentrations [9,13,16,[23][24][25][26][27][28][29], and (4) military range soil concentrations. Some reference values, as well as limits for PTE and CM concentrations in soils, are summarized in Tables 1 and 2, respectively.…”
Section: Generic Limits and Legislation For Protection Of Soils And Rmentioning
confidence: 99%
See 2 more Smart Citations
“…The soil concentrations of contaminants in military zones and war-impacted areas in literature have been typically compared to various types of defined values: (1) background soil concentrations [13,[15][16][17][18][19][20], (2) agricultural soil concentrations [9,17,21,22], (3) generic industrial, urban, and/or recreational soil concentrations [9,13,16,[23][24][25][26][27][28][29], and (4) military range soil concentrations. Some reference values, as well as limits for PTE and CM concentrations in soils, are summarized in Tables 1 and 2, respectively.…”
Section: Generic Limits and Legislation For Protection Of Soils And Rmentioning
confidence: 99%
“…Numerous studies have reported elevated concentrations of PTEs in soil samples collected from war-impacted areas and military training grounds [6,7,9,13,[15][16][17][19][20][21][22][23][24][26][27][28][29][63][64][65][66][67][68][69][70] with their reported values summarized in Table 3.…”
Section: Soil Contamination By Potentially Toxic Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the risk element contents in soils did not show any significant differences between the individual locations, the median values tended to higher levels in the soils at Location A, the oldest deposit. Denton et al[32] monitored the soil risk impact of metallic debris (residues of military hardware, etc.) at WWII dumpsites.…”
mentioning
confidence: 99%